Illumination of Molecular Pathways in Multiple Sclerosis Lesions and the Immune Mechanism of Matrine Treatment in EAE, a Mouse Model of MS - Dou, Mengmeng; Zhou, Xueliang; Li, Lifeng; Zhang, Mingliang; Wang, Wenbin; Wang, Mengru; Jing, Yilei; Ma, Rui; Zhao, Jie; Zhu, Lin (Frontiers in Immunology, 2021)
The etiology of multiple sclerosis (MS) is not clear, and the treatment of MS presents a great challenge. This study aimed to investigate the pathogenesis and potential therapeutic targets of MS and to define target genes of matrine, a quinolizidine alkaloid component derived from the root of Sophorae flavescens that effectively suppressed experimental autoimmune encephalomyelitis (EAE), an animal model of MS. To this end, the GSE108000 gene data set in the Gene Expression Omnibus Database, which included 7 chronic active MS lesions and 10 control samples of white matter, was analyzed for differentially expressed genes (DEGs). X cell was used to analyze the microenvironmental differences in brain tissue samples of MS patients, including 64 types of immune cells and stromal cells. The biological functions and enriched signaling pathways of DEGs were analyzed by multiple approaches, including GO, KEGG, GSEA, and GSVA. The results by X cell showed significantly increased numbers of immune cell populations in the MS lesions, with decreased erythrocytes, megakaryocytes, adipocytes, keratinocytes, endothelial cells, Th1 cells and Tregs. In GSE108000, there were 637 DEGs, including 428 up-regulated and 209 down-regulated genes. Potential target genes of matrine were then predicted by the network pharmacology method of Traditional Chinese medicine, and 12 key genes were obtained by cross analysis of the target genes of matrine and DEGs in MS lesions. Finally, we confirmed by RT-PCR the predicted expression of these genes in brain tissues of matrine-treated EAE mice. Among these genes, 2 were significantly downregulated and 6 upregulated by matrine treatment, and the significance of this gene regulation was further investigated. In conclusion, our study defined several possible matrine target genes, which can be further elucidated as mechanism(s) of matrine action, and novel targets in the treatment of MS.